Transcultural mediation programme in a paediatric hospital in France: qualitative and quantitative study of participants’ experience and impact on hospital costs - Isabelle Durand-Zaleski; Jonathan Lachal; Mélanie Escaich; Serge Bouznah; Pascale De Lonlay; Pierre Canoui; Marie-Rose Moro; Clémence Rousselle (BMJ Open)
Objective In France, immigrants with chronic diseases encounter numerous difficulties in gaining access to care and then in its initiation and organisation, difficulties only partly explained by socioeconomic factors. A transcultural mediation consultation programme has been set up in Necker Hospital in Paris to help families and professionals deal with these situations. The objective of this study was to assess the economic impact and the experience of this consultation.Design Qualitative and quantitative descriptive study.Setting This study of inpatients treated at Necker Hospital included those whose families participated in transcultural mediation in 2014 through 2016.Participants The first portion of the study applied quantitative methods and compared hospital costs before and after the mediation from the patients' records and accounting data for 15 cases. The qualitative portion analysed 15 semistructured interviews of physicians and families after the mediation, and a focus group of three psychologists.Results The results show a systematic reduction in costs after mediation, associated with fewer emergency hospitalisations and the shift of care toward less specialised facilities, calmer relationships between families and professionals, improved mutual understanding and increased confidence by the professionals in the families' ability to manage the treatment.Conclusion Transcultural mediation can benefit both patients and the healthcare system and may be useful for other hospitals that care for socially and culturally diverse patients.